How to do theory (BPub.,lackwell, 2006)
"Using classic literary texts, including Keats's Ode on a Grecian Urn, Spenser's The Shepheardes Calender, and T.S. Eliot's The Waste Land, Iser shows what a work of art looks like if viewed in terms of each of the theories concerned. He presents the different theories objectively, leaving it up to readers to decide which, if any, they subscribe to. In this way, he defuses students' fear of theory and demonstrates the potential of different theories for interpreting texts."--Jacket.